How Does Personalization by Artificial Intelligence on TikTok Influence Purchase Intention? - Meiliya Anjelita; Juniwati Juniwati; Bintoro Bagus Purmono; Wenny Pebrianti; Pramana Saputra (Jurnal Mantik, 2023)
The rise of technology has brought about a surge in internet-based services, shaping social media into a platform for both promotion and online commerce. This study aims to assess the influence of artificial intelligence-driven personalization on purchase intention within the context of TikTok's social media platform. The variables examined in this study encompassed the impact of perceived usefulness, perceived ease of use, and attitude toward personalization on purchase intention within TikTok. This study employs Structural Equation Modeling (SEM) and AMOS 22 statistical software to examine the association between the independent and dependent variables to provide empirical evidence supporting the formulated hypothesis. The data collection methodology employed in this study was a questionnaire administered to a sample of 206 respondents, selected using purposive sampling. The results of this study indicate that the perceived usefulness and perceived ease of use personalization by artificial intelligence have a notable and favorable influence on individuals' attitudes toward personalization. The attitude towards personalization also exhibits a strong influence on purchase intention. Meanwhile, the attitude towards personalization mediates between the perceived usefulness of personalization by artificial intelligence and the perceived ease of use of personalization by artificial intelligence concerning purchase intention.